Mulheres e militância no Espírito Santo: encontros e confrontos durante a ditadura militar - Nascimento, Ingrid Faria Gianordoli (2006)
The military dictatorship period, which began in 1964 and lasted until 1985, marked by a succession of political, economical, and social changes, also characterized itself by the gradual and intense politico-social repression towards its antagonists. In this scenery, is remarkable the political activism of women antagonists to the regime. Transforming the social context and being transformed by it, these women, then, both within the political sphere and within gender relations, broke traditional code of conduct and proposed, instead, alternative forms to live the feminine condition. We aimed in this investigation to focus the psychosocial aspects, mainly those related to the identification processes, implied in the interconnection between gender relations and politics in women activism opposing against the dictatorial regime, from 1964 until 1985, in the state of Espírito Santo, Brazil. With this objective, individual interviews were conducted with 09 women who participated of organizations which clearly stood as resistance against the military dictatorship between 1964 and 1973. All interviewees were university students engaged in the student movement and affiliated, for some period, to clandestine political parties. They have also been imprisoned for periods which vary from one month to one year. We attempted to investigate the life trajectory of these women from infancy until now. The information was subjected to the phenomenological method for psychological investigation and reorganized in narratives that attempt to identify the particularities and the common points in the related experiences. The data analysis tried to highlight, from the accounts of their trajectories, the dynamics of the elements in play for the constitution of the identity of these women. Among these elements are the individuation and the autonomy projects; the motivations for the activism; the conflicts between individual and collective projects; the experience on limit situations, such as imprisonment and torture; marriage; maternity; evaluations of the period; and current political participation. In the reconstruction of their trajectories, the former activists reveal the complex interactions between motivations and choices, and uncommon, sometimes hard, experiences that result from them. The complexity of this interaction, on the other hand, contributes, and, evidently, continues contributing, for the constitution of their identities.